Reducing Phubbing Behavior Through Group Counseling with Positive Self-Talk Techniques - Indri Ariani; Nefi Darmayanti (MASI Mandiri Edukasi, 2025)
This study aims to determine the effectiveness of group counseling services using positive self-talk techniques to reduce phubbing behavior among junior high school students. This research employs a quantitative approach with a pre-experimental one-group pretest-posttest design. The research participants consisted of 8 students from class VIII-7 of SMP Negeri 1 Bilah Hulu with high phubbing scores based on pretest results. The intervention was carried out through 4 group counseling sessions for 45 minutes per session. The Wilcoxon Signed-Rank Test analysis showed that all participants experienced a significant decrease in phubbing behavior scores, with a Z value of -2.536 and an Asymp. Sig. (2-tailed) significance of 0.011 (p < 0.05). All data fell into the category of negative ranks, meaning no participants had scores that remained the same or increased. The results of this study indicate that group counseling services using positive self-talk techniques have been proven to be very effective in reducing phubbing behavior among eighth-grade students at SMP Negeri 1 Bilah Hulu. The positive self-talk technique can help participants increase self-awareness of their phubbing habits, manage the urge to misuse smartphones, and improve direct communication skills with friends or family. Therefore, group counseling services with positive self-talk techniques are recommended for guidance teachers as an optimal and sustainable intervention strategy to reduce phubbing and improve self-control and the quality of students' social interactions in the digital era.